Urgensi Penegasan Kewenangan Pengadilan Hubungan Industrial Dalam Penyelesaian Perselisihan Hubungan Industrial - Kristiani, Enny; Vic S., Binsar Jon (JURNAL RETENTUM, 2023)
Legal reform in the regulation of the authority of the Industrial Relations Court (PHI) is an important step to increase the effectiveness of industrial relations dispute resolution in Indonesia. Current legal limitations, such as the lack of court authority in enforcing decisions, as well as challenges in coordination between institutions, slow down the dispute resolution process. Therefore, reforms that include strengthening the authority of the court, the application of technology in the judicial system, and the harmonization of laws and regulations are expected to create clearer legal certainty and improve social justice. This reform will also accelerate the dispute resolution process, ensure more effective enforcement of decisions, and create more harmonious industrial relations between workers and employers, which ultimately supports sustainable economic development in Indonesia.